An overview of the utilization and method for improving pozzolanic performance of agricultural and industrial wastes in concrete - Mohammad I, AlBiajawi; Rahimah, Embong; Khairunisa, Muthusamy (Elsevier Ltd, 2021)
The concept of utilizing industrial and agricultural waste materials in concrete contributes to recompensing lacking natural resources, solving the waste disposal problem, and finding alternative techniques to protect nature. Environmental awareness regarding potential harmful effects has significantly increased, and, thus, recycling or using agricultural and industrial waste by-products has become an increasingly attractive alternative for waste disposal. Several related studies investigated the utilization of waste materials and by-products like coal bottom ash, rice husk ash, coconut shells, plastic, glass, and wood. In this paper, a thorough assessment has been conducted about the industrial and agricultural waste substances that can be effectively utilized in concrete as an alternative to cement or aggregate in the concrete mixture. This paper also aims to promote utilizing wastes by improving pozzolanic performance and material properties as part of concrete constituents.